Constructing Irish National Identity - Kane, A. author. aut Link
XVIII, 280 p. 2 illus.
Keywords: Author Anne Kane analyzes the intertwined cultural, political and social transformations that occur during historical events by focusing specifically on the case of the Irish Land War, a pivotal event in the formation of the modern Irish nation.